Aquaculture, Innovation and Social Transformation - Culver, Keith; Castle, David (Dordrecht : Springer Netherlands, 2009)
Aquaculture, Innovation and Social Transformation presents and interprets Canadian and international perspectives on the debate over the future of aquaculture in Canada. Original chapters examine: animal welfare; knowledge management and intellectual property; environmental sustainability; local, traditional, and aboriginal knowledge; consumers; and integrated coastal zone management. Authors of principal chapters are drawn from Canadian and European universities, while commentators are drawn from Canadian government and private sectors. This structure results in a deliberately engineered collision of diverse habits of thought and dissimilar bases of knowledge. In that collision the problems, options, and possible future of aquaculture are both explicitly argued, and shown in the interaction between authors and perspectives. Of particular note is the inclusion of perspectives written by First Nations members, and an epilogue from the comparative perspective of US experience. This book will be of interest to those concerned with the social effects of intensification of food production, food security, scholars of technology, environment-focussed researchers, and anyone who cares about the future of the world's oceans. This volume is unique in its depiction of the nature and complexity of the social dimensions of the choice to farm the ocean.
includes bibliographical references.
Keywords: Life sciences; Ethics; Aquatic biology; Wildlife management; Sustainable development; Life Sciences; Fish & Wildlife Biology & Management; Freshwater & Marine Ecology; Ethics; Sustainable Development